Neurofilaments contribution in clinic: state of the art - Delaby, Constance; Bousiges, Olivier; Bouvier, Damien; Fillée, Catherine; Fourier, Anthony; Mondésert, Etienne; Nezry, Nicolas; Omar, Souheil; Quadrio, Isabelle; Rucheton, Benoit; Schraen-Maschke, Susanna; van Pesch, Vincent; et al. (Frontiers in Aging Neuroscience, 2022)
Neurological biomarkers are particularly valuable to clinicians as they can be used for diagnosis, prognosis, or response to treatment. This field of neurology has evolved considerably in recent years with the improvement of analytical methods, allowing the detection of biomarkers not only in cerebrospinal fluid (CSF) but also in less invasive fluids like blood. These advances greatly facilitate the repeated quantification of biomarkers, including at asymptomatic stages of the disease. Among the various informative biomarkers of neurological disorders, neurofilaments (NfL) have proven to be of particular interest in many contexts, such as neurodegenerative diseases, traumatic brain injury, multiple sclerosis, stroke, and cancer. Here we discuss these different pathologies and the potential value of NfL assay in the management of these patients, both for diagnosis and prognosis. We also describe the added value of NfL compared to other biomarkers currently used to monitor the diseases described in this review.